Analisis Putusnya Perkawinan Akibat Pertengkaran Karena Media Sosial di Pengadilan Agama Kota Kisaran - Sani, Indira Aprilia; Pulungan, Sahmiar; Nurcahaya, Nurcahaya (Kamaya: Jurnal Ilmu Agama, 2023)
Indications of problems in marriage that cause the breaking of ties in a marriage that occur because social media always has a very risky impact on the lives of both husband and wife and children. So this research aims to find out the causes of the conflict that resulted in the breakdown of marriages at the Kisaran Religious Court. Second, to find out the considerations of the Panel of Judges at the Kisaran Religious Court in deciding on the conservation of social media as a cause of conflict which has an impact on the breakdown of marriages in decision Number: 2245/Pdt.G/2020/PA.Kis, Number: 1187/Pdt.G/2021/PA .Kis, Number: 2296/Pdt.G/2022/PA.Kis. Third, to find out the view of the Islamic Law Compilation regarding the protection of social media as a cause of conflict. This research was carried out at the Kisaran Class I B Religious Court Office located in Asahan Regency. This type of research is field research which is carried out using a phenomenological approach. This research data collection technique is through interviews, observation, documentation. The results of this research can be seen in the case decisions by the Panel of Judges at the Kisaran Religious Court in 2020 to 2022. The high number of divorces that occur is due to several reasons, namely infidelity (third person), domestic violence (KDRT) and the habit of participating in online gambling as well as economic problems. families whose problem sources originate from the Facebook, Twitter, Instagram and WhatsApp networks, who are not good at utilizing these networks, resulting in conflict and ending in divorce at the Kisaran Religious Court.